Produk Hukum Islam dan Implementasinya di Indonesia - Nurahmad Nurahmad; Marilang Marilang; Musyfikah Ilyas (AHKAM, 2025)
Islamic legal products play a strategic role in shaping Indonesia’s pluralistic and dynamic national legal system. This study aims to analyze the concepts and characteristics of Islamic legal products, evaluate their implementation within the national legal framework, and identify the supporting and inhibiting factors affecting their application. A qualitative method was employed using a normative-juridical and socio-legal research approach, involving analysis of primary and secondary sources such as statutory regulations, fatwas, Islamic legal literature, and institutional documents. The findings reveal that Islamic legal products possess a high degree of flexibility and adaptability, grounded in the core principles of justice, public interest (maslahah), and balance, which are contextually responsive to contemporary socio-economic dynamics. Their implementation in the national legal system is realized through normative integration into formal regulations and social acceptance via institutional practices, particularly in the areas of Islamic banking, fintech, and the management of zakat and waqf. Supporting factors include adaptive regulations, clear fatwa guidelines, and growing public awareness. In contrast, inhibiting factors consist of legal system pluralism, limited codification of Islamic law, and low legal literacy among the public. This study concludes that stronger synergy between Islamic and national law is essential to building a responsive, inclusive, and sustainable legal system. Collaboration among fatwa institutions, regulators, academics, and society is key to achieving regulatory harmonization that addresses the challenges of modernization and digital transformation while ensuring justice and social welfare for all.